In search of the lost Orient : an interview - Roy, Olivier, 1949- (Columbia University Press, 2017)
Olivier Roy is one of the world's leading experts on political Islam. But he is not only a scholar--he is also a traveler. Roy's keen and iconoclastic insights emerge from a lifetime of study combined with intrepid exploration through Afghanistan and Central Asia. In this book-length interview, Roy tells the lively and colorful story of his many adventures and discoveries in a variety of social and political settings and how they have come to shape his understanding of the Islamic world and its complex recent history. In Search of the Lost Orient is a candid, personal account of the experiences that led Roy to challenge his youthful ideas of an untouched, romanticized East and build a new intellectual framework to better understand and cohabit with the religions, politics, and cultures of the East, West, North, and South. In conversation with Jean-Louis Schlegel of the French magazine Esprit, Roy offers insight into the key themes of his career. Roy's immersion in the complexities of many Central Asian territories started him on his critique of the idea of an essentialized Islam. Alongside tales of backpacking from Paris to Kabul, his Afghan decade during the Soviet invasion, and official travel to post-Soviet Central Asia in the 1990s, Roy reflects on the nature of political and humanitarian engagement in this part of the world. He recounts his formative years, education, and developing political commitments and speaks to his evolving place within France's shifting intellectual and religious cultures. This book outlines Roy's lifelong practice--a combination of deliberate research goals and chance encounters--that examines Islam, immigration, and, more broadly, the future of cultures, religions, and secularism in the face of globalization. Both a significant intellectual autobiography and a compelling travelogue through some of the world's pivotal places, In Search of the Lost Orient offers a striking testimony to the many facets of an exceptional thinker.